Patient compliance: A concept analysis - Saowaluk Thummak; Wassana Uppor; La-Ongdao Wannarit (Belitung Raya Foundation, Indonesia, 2023)
Background: Patient compliance with regimens is one of the most researched and least-understood behavioral concerns in the healthcare profession due to the many meanings employed in multidiscipline over time. Thus, a thorough examination of the idea of patient compliance is necessary. Objective: This paper aims to explore and identify the essence of the term patient compliance to achieve an operational definition of the concept. Method: Walker and Avant’s eight-step approach was used. A literature search was conducted using keywords of patient compliance AND healthcare profession from five databases: PubMed, Medline, CINAHL, ProQuest, ScienceDirect, and Cochrane database, published from 1995 to 2022. Results: The attributes of patient compliance include 1) self-care behavior, 2) following health recommendations, and 3) willing collaboration with health professionals. Antecedents of patient compliance were characteristics of therapeutic regimens, communication of health advice, and patients’ attitudes toward professional recommendations. Consequences include improved clinical outcomes, quality of life, and lifestyle or behavior modification. Conclusion: This concept analysis offers a valuable perspective on patient compliance that guides the nursing practice in providing better interventions to promote compliance among patients.